Transformational Leadership In Building A Sustainable Organization: Qualitative Study at PT Pos Indonesia (Persero) - Turyandi, Itto; Veranita, Mira; Wahyudi; Gunardi (International Journal Administration, Business & Organization, 2025)
In facing the challenges of globalization, organizations are not only required to achieve financial benefits, but also to ensure sustainability in social and environmental aspects. This study explores the role of transformational leadership in building a sustainable organization, with a case study at PT Pos Indonesia (Persero). Through a qualitative approach, this study analyzes the impact of transformational leadership on innovation, employee engagement, and organizational culture that supports sustainability. The results of the study indicate that transformational leadership contributes significantly to creating a clear long-term vision, encouraging employee empowerment, and building a positive organizational culture. The main factors that influence the effectiveness of this leadership include effective communication, empathy, employee empowerment, appreciation for contributions, and delivery of a clear vision. These findings provide insights for organizational leaders in developing responsive and adaptive leadership strategies to future business challenges